AB1008 AGE DEPENDENT SAFETY AND EFFICACY OF COLCHICINE TREATMENT FOR FAMILIAL MEDITERRANEAN FEVER IN CHILDREN. (June 2019) - Levinsky, Yoel; Goldberg, Ori; Peled, Orit; Koren, Gideon; Harel, Liora; Amarilyo, Gil
Abstract : Background: Colchicine has been found to be highly effective for the treatment of familial Mediterranean fever (FMF). However, it is FDA-approved only for children older than 4 years owing to the lack of studies in younger children. Objectives: Our tertiary pediatric rheumatology department routinely uses colchicine even in very young children with FMF. The aim of the study was to evaluate its safety and efficacy in children with FMF <4 years old. Methods: The departmental database was searched for all children diagnosed with FMF between 2010-2018. Those who started treatment with colchicine before age 4 years were identified and matched by MEFV variant to children who started treatment at age 4-8 years. Drug efficacy was assessed by the improvement in the frequency and duration of attacks. Adverse events were assessed according to the Rheumatology Common Toxicity Criteria ver. 2.0. Results: The cohort included 89 patients with FMF: 41 first treated before age 4 years, and 48 first treated at age 4-8 years. Rates of complete response to colchicine were 61% in the younger group and 60.4% in the older group. Corresponding rates of partial remission were 24.4% and 29.2% ( p =0.77). The most frequent adverse event was diarrhea, with a prevalence of 24.4% in the younger group and22. 9% in the older group (p=0.87). There were no significant between-group differences in other adverse events. Conclusion: Colchicine is equally effective and safe for use in patients with FMF under 4 years old, with no difference in response from older pediatric patients. IQR-interquartile range Values are n(%) unless otherwise indicated. AEs – adverse events * RCTC- Rheumatology Common Toxicity Criteria, version 2.0 for AE severity:0-no, 1– mild, 2 – moderate, 3 – severe, 4 – life-threatening Values are n (%) unless otherwise indicated. § Due to statistical limitations, Statistic analysis (Fisher's exact test) was performed between No AEs & RCTC score 1 and RCTC score 2-4 in the respected age groups. † Data available for 34 patients. ‡ Data available for 43 patients. Disclosure of Interests: None declared